2023
DOI: 10.3390/su151411337
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis between Heuristic and Data-Driven Water Management Control for Precision Agriculture Irrigation

Abstract: Modeling and control theory applied to precision agriculture irrigation systems have been essential to reduce water consumption while growing healthy crops. Specifically, implementing closed-loop control irrigation based on soil moisture measurements is an effective approach for obtaining water savings in this resource-intensive activity. To enhance this strategy, the work presented in this paper proposed a new set of water management strategies for the case in which multiple irrigation areas share a single wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…García et al [10] applied control theory to precision agriculture irrigation systems, based on soil moisture measurements, for obtaining water savings. The developed water allocation algorithms were based on real-time computing, such as dynamic priority and feedback scheduling.…”
Section: Heuristic and Data-driven Water Management For Precision Agr...mentioning
confidence: 99%
“…García et al [10] applied control theory to precision agriculture irrigation systems, based on soil moisture measurements, for obtaining water savings. The developed water allocation algorithms were based on real-time computing, such as dynamic priority and feedback scheduling.…”
Section: Heuristic and Data-driven Water Management For Precision Agr...mentioning
confidence: 99%
“…In addition, saline-alkali soil is mainly distributed in arid and semiarid areas, and agricultural production is often accompanied by water stress and other problems [14]. Some studies [15] have found that a small amount of multiple irrigation can make soil water movement mainly unsaturated and maintain the total soil water potential at a high level to compensate for the decreased osmotic potential due to the presence of salt. This is conducive to improving the crop root environment, promoting the water absorption of crop roots, and realizing the sustainability of crop yield.…”
Section: Introductionmentioning
confidence: 99%